2018
DOI: 10.15666/aeer/1605_65896605
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medicinal Plants by Livestock Farmers in a Local Municipality in Vhembe District, South Africa

Abstract: Respondents (n = 180) from Mutale municipality, Limpopo Province, South Africa, were interviewed so as to assess the factors affecting the use of medicinal herbs in treatment of livestock diseases. A significantly greater proportion of males (79.8%) than females (52.7%) preferred a combination of treatment methods (P < 0.05). A significantly greater proportion of females (36.8%) than males (10.6%) preferred using medicinal herbs only (P < 0.05). There was no significant difference in the proportions of males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The male supremacy in ethnoveterinary knowledge may be because of cultural expectations that when a woman marries, she will not inherit the knowledge of the household. These findings are in conformity with several previous researchers who observed that knowledge of medicinal plants is mostly transmitted from father to son and limited to older people (Ahmad et al 2016;Bartha et al 2015;Chitura et al 2018;Garedew & Abebe 2018). High number of respondents who can read and write can play a major role on improving animal health-related diseases through recordkeeping, measurement of dosage, adoption and practice of new technologies that may enhance livestock production under communal sector.…”
Section: Discussionsupporting
confidence: 90%
“…The male supremacy in ethnoveterinary knowledge may be because of cultural expectations that when a woman marries, she will not inherit the knowledge of the household. These findings are in conformity with several previous researchers who observed that knowledge of medicinal plants is mostly transmitted from father to son and limited to older people (Ahmad et al 2016;Bartha et al 2015;Chitura et al 2018;Garedew & Abebe 2018). High number of respondents who can read and write can play a major role on improving animal health-related diseases through recordkeeping, measurement of dosage, adoption and practice of new technologies that may enhance livestock production under communal sector.…”
Section: Discussionsupporting
confidence: 90%
“…C. quadrangularis Linn. is widely used for the treatment of multiple ailments, such as controlling ticks [ 4 ], promoting bone fracture and tissue healing [ 33 ], treatment of Newcastle disease [ 34 ], retained placenta [ 35 ] and worm infestation [ 36 ]. According to the literature, some popular plants that participants identified have been reported to possess anthelmintic properties amongst other medicinal uses; A. anthelminthica Brongn [ 37 ], S. birrea [ 38 ], T. emetica [ 39 ], A. ferox [ 13 ], V. neocorymbosa [ 40 ], and S. pinnata [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adapting local knowledge of plants and the practices associated with this has been well-documented in the literature (Mayer et al 2017 ; Chitura et al 2018 ; Kambizi 2016 ). The totality of the indigenous local animal healthcare beliefs and practices is popularly referred to as ethno-veterinary medicine (EVM), and the practice is reported in various continents in both developed and developing countries (Vougat Ngom and Foyet 2022 ).…”
Section: Importance Of Indigenous Knowledgementioning
confidence: 99%